2022
DOI: 10.3389/fmicb.2022.1066807
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a compound microbial agent for biocontrol against Fusarium wilt of banana

Abstract: Banana wilt caused by Fusarium oxysporum f. sp. cubense has devastated a large number of banana plantations worldwide. Biological control is a possible method to conquer this disease. However, the control effect was often low and unstable while a single biocontrol strain had been applied in the field. Therefore, this study aimed to construct an effective compound microbial agent to control Fusarium wilt of banana (FWB) in the field. In addition to it, the compounding strategy of combining single strains for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The impact of microbial agents on the water quality of aquaculture system has garnered increasing attention from researchers (Hoseinifar et al, 2023). In the present study, compared to the control, CMA treatment delayed the increase of pH (a decline of 2.96%), improved the DO value (a rise of 4.63%), and inhibited the eutrophication of M. salmoides aquaculture system by decreasing levels of ammonia nitrogen (a decline of 41.75%), nitrite (a decline of 19.35%), total phosphorus (a decline of 9.04%), and total nitrogen (a decline of 22.45%) at 7 d. Meanwhile, the water quality of CMA treated group was better than that of SAM treated group, suggesting that the application of microbial agents effectively improved the water quality of M. salmoides aquaculture system, with CMA treatment yielding superior It has proven that the efficacy of CMA in controlling Fusarium oxysporum in banana surpassed that of SMA, with a more distinct strain classification leading to enhanced control effects (Du et al, 2022), corroborating our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of microbial agents on the water quality of aquaculture system has garnered increasing attention from researchers (Hoseinifar et al, 2023). In the present study, compared to the control, CMA treatment delayed the increase of pH (a decline of 2.96%), improved the DO value (a rise of 4.63%), and inhibited the eutrophication of M. salmoides aquaculture system by decreasing levels of ammonia nitrogen (a decline of 41.75%), nitrite (a decline of 19.35%), total phosphorus (a decline of 9.04%), and total nitrogen (a decline of 22.45%) at 7 d. Meanwhile, the water quality of CMA treated group was better than that of SAM treated group, suggesting that the application of microbial agents effectively improved the water quality of M. salmoides aquaculture system, with CMA treatment yielding superior It has proven that the efficacy of CMA in controlling Fusarium oxysporum in banana surpassed that of SMA, with a more distinct strain classification leading to enhanced control effects (Du et al, 2022), corroborating our results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, improving water quality is of great significance for the cultivation of M. salmoides. Recent have revealed that the of microbial agents alters the overall quality of soil by modifying the bacterial community structure and the chemical properties (Du et al, 2022;Ahsan et al, 2023;Wang et al, 2023). The impact of microbial agents on the water quality of aquaculture system has garnered increasing attention from researchers (Hoseinifar et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Trichoderma spp. is by far the most studied fungi for controlling FWB ( Bubici et al., 2019 ; Damodaran et al., 2020 ; Du et al., 2022 ; Zhang et al., 2022 ). Being a multipurpose microorganism, Trichoderma spp., utilizes direct antagonism and competition in the rhizosphere, colonizes plant roots (externally and/or as an endophyte), and has the capacity to promote plant growth and prime local and systemic defense responses against biotic stresses.…”
Section: Biological Controlmentioning
confidence: 99%
“…In China, where Foc TR4 is widely distributed and has devastated thousands of hectares of bananas, biocontrol strategies based on the combination of microorganisms have also been explored with encouraging results under field conditions ( Lin and Ho, 2021 ; Du et al., 2022 ; Zhu et al., 2023 ).…”
Section: Biological Controlmentioning
confidence: 99%